Correlation Between Fear of Postoperative Pain and the Use of Analgesics Among Elderly Patients in Turkey - Topal Hançer, Ayşe (Africa Journal of Nursing and Midwifery, 2023)
In elderly patients, preoperative assessment of pain fear could provide essential information for improving perioperative care and could be the first step toward targeted pain management. This study aimed to determine the effect of fear of postoperative pain and the use of analgesics among elderly patients in Turkey. The method used was a descriptive cross-sectional study with 231 elderly patients. In this study, the levels of fear of pain were significantly higher in those who had a history of surgery, experienced severe pain, and had a feeling of fear before surgery (p<. 05). The mean pain Visual Analog Scale (VAS) first day postoperatively was 8.20±1.69, and the mean VAS second day postoperatively was 5.20±1.51. It was determined who received tramadol (opioid) 100 mg intravenously (IV) on the first and second postoperative day with a significantly higher mean score on the fear of pain (p<. 05). It was determined that pain intensity and the rate of analgesic use on the first and second postoperative days were positively correlated with fear of pain (p<. 001). This research demonstrated that as the elderly patients’ pain fear increased, postoperative pain severity and amount of analgesia increased. Therefore, reducing the fear of pain, which is one of the main factors in pain, is essential in pain management. Evaluation of postoperative pain not only in terms of drug intervention but also in terms of other factors that modulate pain, such as fear of pain—it is thought that the elderly, who constitute a risky group in terms of analgesic use, can provide convenience in pain management.